Development and characterization of EST‐SSR markers for Carex angustisquama (Cyperaceae), an extremophyte in solfatara fields. (19th October 2018) - Nagasawa, Koki; Setoguchi, Hiroaki; Maki, Masayuki; Goto, Hayato; Fukushima, Keitaro; Isagi, Yuji; Sakaguchi, Shota
Abstract : Premise of the Study: Expressed sequence tag–simple sequence repeat (EST‐SSR) markers were developed for Carex angustisquama (Cyperaceae) to investigate the evolutionary history of this plant that is endemic to solfatara fields in northern Japan. Methods and Results: Using RNA‐Seq data generated by the Illumina HiSeq 2000, 20 EST‐SSR markers were developed. Polymorphisms were assessed in C. angustisquama and the closely related species C. doenitzii and C. podogyna . In C. angustisquama, many loci were monomorphic within populations; the average number of alleles ranged from one to five, and levels of expected heterozygosity ranged from 0.000 to 0.580, while all markers were polymorphic in a population of C. doenitzii . This indicates that low genetic polymorphism of C. angustisquama is likely due to the species' population dynamics, rather than to null alleles at the developed markers. Conclusions: These markers will be used to assess genetic diversity and structure and to investigate evolutionary history in future studies of C. angustisquama and related species.